Double-stranded RNA induces mRNA degradation in Trypanosoma brucei. - Ngô, H; Tschudi, C; Gull, K; Ullu, E (1998)
Double-stranded RNA (dsRNA) recently has been shown to give rise to genetic interference in Caenorhabditis elegans and also is likely to be the basis for phenotypic cosuppression in plants in certain instances. While constructing a plasmid vector for transfection of trypanosome cells, we serendipitously discovered that in vivo expression of dsRNA of the alpha-tubulin mRNA 5' untranslated region (5' UTR) led to multinucleated cells with striking morphological alterations and a specific block of cytokinesis. Transfection of synthetic alpha-tubulin 5' UTR dsRNA, but not of either strand individually, caused the same phenotype. On dsRNA transfection, tubulin mRNA, but not the corresponding pre-mRNA, was rapidly and specifically degraded, leading to a deficit of alpha-tubulin synthesis. The transfected cells were no longer capable of carrying out cytokinesis and eventually died. Analysis of cytoskeletal structures from these trypanosomes revealed defects in the microtubules of the flagellar axoneme and of the flagellar attachment zone, a complex cortical structure that we propose is essential for establishing the path of the cleavage furrow at cytokinesis. Last, dsRNA-mediated mRNA degradation is not restricted to alpha-tubulin mRNA but can be applied to other cellular mRNAs, thus establishing a powerful tool to genetically manipulate these important protozoan parasites.